2020
DOI: 10.1186/s13020-020-00324-y
|View full text |Cite
|
Sign up to set email alerts
|

The curative effects of the traditional Chinese herbal medicine “Jinchuang ointment” on excisional wounds

Abstract: Background “Jinchuang ointment” is a traditional Chinese herbal medicine for external incised wounds. This herbal medicine has been successfully used to treat patients with diabetic foot ulcers and pressure sores in Taiwan for several decades. We previously examined its biological activities on cell-based in vitro assay platforms. Because some patients refused to use animal-derived ingredients ointment during our clinical practice, the efficacy of plant oil-based reconstituted “Jinchuang ointment” was also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…e pigs were 4.5 months old (average weight: 18.0 kg) and had similar body shapes. Each animal was maintained as described previously [7].…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…e pigs were 4.5 months old (average weight: 18.0 kg) and had similar body shapes. Each animal was maintained as described previously [7].…”
Section: Animal Experimentsmentioning
confidence: 99%
“…After fixation, the tissues were trimmed, embedded, and divided into 5 mm thick sections and placed on glass slides (Immuno Coated slide, MUTO, Japan). ese paraffin-embedded sections were treated with hematoxylin and eosin (H & E), Masson-trichrome (MT) stains, and immunohistochemistry (IHC) stain, as reported previously [7].…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional Chinese herbal medicine, “Jinchuang ointment,” has excellent efficacy in the treatment of chronic non-healing wounds in patients with diabetes [ 1 ]. Its efficacy was also examined and confirmed in a porcine excisional wound model [ 2 ]. This herbal medicine is also effective for ulcers in people with leprosy (Hansen’s disease) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results indicated that the Jinchuang ointment-treated group had a much stronger blood flow flux in porcine excisional wound sites than the control group, as shown by laser Doppler imaging analysis [ 2 ]. First, we attributed these results to the angiogenic activity of dragon blood during wound healing.…”
Section: Introductionmentioning
confidence: 99%